Mechanism of hot spots formation in pentaerythritol tetranitrate upon excitation by the first harmonic of a neodymium laser; Energy Fluxes and Radiation Effects (EFRE-2016) - Oleshko V. I. Vladimir Ivanovich; Tsipilev V. P. Vladimir Papilovich; Zarko V. Vladimir; Kozubova M. Marina (2016, 2016)
Title screen